Elphie : a Wicked childhood [large type] - Maguire, Gregory (Maguire, Gregory. Wicked years, 2025)
What happened to young Elphaba before her witchy powers took hold in Wicked? Almost 30 years after the publication of the original novel, for the first time Gregory Maguire reveals the story of prickly young Elphie, the future Wicked Witch of the West-setting the stage for the blockbuster international phenomenon that is Wicked: The Musical. Elphaba, the Wicked Witch of the West, will grow to have a feisty and somewhat uncompromising character in adult life. But she is always a one-off, from her infancy; Elphie is the riveting coming-of-age story of a very peculiar and relatable young girl. Young Elphie is shaped and molded by the behaviors of her promiscuous mother, Melena, and her pious father, Frex. She suffers ordinary childhood jealousies when her sister, saintly Nessarose, and brother, junior felon Shell, arrive. She first encounters the mistreatment of the Animal populations of Oz, which live adjacent to but not intertwined with human settlements, haunted by a Monkey and receiving aid from Dwarf Bears. She thrashes through her first bruising attempts at friendship, a possible lifeline from her tricky family life. And she gleans the benefits of an education, haphazard though it must be-until she arrives at the doors of Shiz University, about to meet the radiant creature that is Galinda. Elphie is destined to be a witch; she bears the markings from childhood-most evidently in her green skin but more obscurely and profoundly in her cunning and perhaps amoral behaviors, as she seeks to make do, to slip by, to sneak out, to endure, and to aspire.